(untitled) (Proceedings of International Educators Conference, 2024)
It has been established that haplogenin – 7 – glycoside increases mitochondrial respiration of rat liver. Thus the ADP/O quotient increases slightly by glutamate, and by succinate on the contrary, decreases imperceptibly.